2014
DOI: 10.4321/s0213-61632014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and functionality: the impact of delirium on the level of functioning

Abstract: -Background and Objectives: Studies have shown showed that delirium affects the long-term functional status, however, the acute effect of delirium on functioning has been less documented. The purpose of this analysis was to examine the acute impact of delirium on the level of functioning.Methods: All patients were recruited at the Memorial Sloan Kettering Cancer Center (MSKCC). The Memorial Delirium Assessment Scale (MDAS) and Karnofsky scale of Performance Status (KPS) were recorded at baseline (T1), 2-3 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Because most atypical antipsychotics such as risperidone can be administered only by the oral route, it may not be surprising that experts recommended the use of haloperidol preferentially, given that it is known that oral administration is not suitable for some patients. In addition, the preference for atypical antipsychotics could result from safety concerns, as several studies have shown that atypical antipsychotics might have a lower propensity than haloperidol to induce extrapyramidal symptoms (Miyaji et al, 2007;Boettger et al, 2015). Second, more than 88% of experts recommended the use of quetiapine over risperidone in the treatment of hyperactive delirium in patients with renal dysfunction who did not also have diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Because most atypical antipsychotics such as risperidone can be administered only by the oral route, it may not be surprising that experts recommended the use of haloperidol preferentially, given that it is known that oral administration is not suitable for some patients. In addition, the preference for atypical antipsychotics could result from safety concerns, as several studies have shown that atypical antipsychotics might have a lower propensity than haloperidol to induce extrapyramidal symptoms (Miyaji et al, 2007;Boettger et al, 2015). Second, more than 88% of experts recommended the use of quetiapine over risperidone in the treatment of hyperactive delirium in patients with renal dysfunction who did not also have diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Ten papers (five studies) 25,35,40,42,56–61 analysed functional recovery over time in the context of delirium, with nine (four studies) observing improvement. Boettger et al 25,56–61 .…”
Section: Resultsmentioning
confidence: 99%
“…As our inclusion criteria did not exclude studies involving interventions, some studies reported change within symptom domains as a result of drug intervention for example, aripiprazole, haloperidol. 25,[56][57][58][59][60] This may have affected the recovery trajectories of symptom domains, for example, functional recovery in the Boettger et al study. 25,[56][57][58][59][60] In these instances, conclusions of symptom recovery may not be entirely generalisable to an acute hospital delirious population, as although haloperidol in small doses is administered in clinical settings to manage severe symptoms (e.g., distress and agitation), use of aripiprazole is not common practice (in the UK), nor is it advised by the NICE guidelines.…”
Section: Strengths and Limitationsmentioning
confidence: 96%
See 1 more Smart Citation
“…The main impacts of delirium includes it increases treatment cost by causing prolonged hospital stay, increases mortality rate, increase burden for nurse and caregivers (11), acute functional decline, causes cognitive declining in older adults, cause falls, ongoing need for care in long term institution, economical impact, distress. (12,19,25,27,(30)(31)(32) Mostly delirium affects for ICU and ICU burn patients 32.3% and 77% respectively. (33,34) delirium also affects more for older people who had surgery.…”
Section: Introductionmentioning
confidence: 99%